Effects Of Environmental Factors On Vibriosis In Seabass (Lates Calcarifer Bloch) At A Floating Cage Culture Farm. - Arulampalam, Premala (1995)

(untitled)
The present study indicates that the evolution of intensive marine cage culture farms in Malaysia can be a potential risk for outbreaks of vibriosis under unfavourable environmental conditions . The cage culture farm harboured significantly higher numbers of bacteria in the sediment and underlying waters compared to the surrounding waters indicating that the farm serves as a reservoir for bacteria. This is due to the rapid build up of organic waste from feed and excretion matter from fish. Vibrios isolated from the cage culture farm were found to be virulent to sea bass fingerling. Intraperitoneal injections of whole live bacterial cells of the chosen isolate , Vibrio alginolyticus caused higher mortalities compared to the extracellular products ( ECP) of the bacteria.In the intramuscular injection ( 1M ) , only whole live bacterial cells of V. alginolyticus caused 50% mortalities when injected into sea bass finger lings .